موقف روسيا الاتحادية من تطورات الأزمة النووية الإيرانية 2005-2008 دراسة تاريخية - محمد سالم احمد الكواز (University of Mosul-college of Basic Education, 2012)
In 2005, Russia entered the deep debate with the Western permanent members of the UN Security Council on the nature of its relations with Tehran government, which showed its intransigence in no cooperation with the International Atomic Energy Agency (IAEA) from 2005. So that increased nuclear crisis worsened after long negotiations failed between Iran and the European Union, more especially after the arrival of President Mahmoud Ahmadinejad to the presidency in Iran in 2005, which deepened the relations with Russia under its former President Vladimir Putin, as well as in the current era of the Russian President Dimitry Medvedev after a relative volatility. Despite entangling interests linking Russia, Iran, and specifically in the nuclear field, the Iranian stand in noncompliance with international laws that raised Western suspicions and even Russia in the peace announced by Iran to develop its nuclear program, has put the Russians in positions very embarrassing. However, driven by the interests and benefits, of Moscow, Russia continued its defense of Iran after refering the Iranian nuclear file from the International Atomic Energy Agency (IAEA) to the UN Security Council, which issued a package of international sanctions against Iran over the years 2006-2008.